Detection of early lung cancer lesions in surgical resections and in bronchial and transbronchial biopsies - Rott, Tomaž (Radiology and oncology (Ljubljana), 2006)
Background. Overall bad progmpsis of lung is mostly due to too late detection of early lung cancer, which may be teated with good success. Therefore different diagnostic methods are developing for more efficient detection of early lung cancer: besides modern radiological, bronchoscopic methods with additional fluorescence techniques, quantitative cytological investigations, also histological and molecular investigations are included. History may reveal early preinvasive lung xcancer lesions, associated early during multistep lung carcinogemesis with molecular genetic changes. Patients and methods. Preinvasive epithelial lung cancer lesions we searched in two groups of patients. In the first group of 316 patients from the period March 2003 - August 2006, 498 bronchial and transbronchial biopsies were examined for squamous metaplasia and dysplasia, carcinoma in situ, and invasive tumours. Inthe second group of 238 patients from the period January 2004 - August 2006,resected primary lung tumours were analysed for preinvasive neuroendocrine tumours and atypical adenomatous hyperplasia. Resuots. The mostfrequent changes in bronchial and transbronchial biopsies were squamous metaplasia (46.5%), simple or goblet cell hyperplasia of the bronchial epithelium (44.3%), malignant tumours (20.66%) and squamous dysplasia (16.1%),but rare carcinoma in situ (0.63%). Diffuse idiopoathic pulmonary neuroendocrine cell hyperplasia was found in 15 (6.3%) cases in the vicinity of 238 resected lung cancer specimens, carcinoid in12 patients (5%), and mostly combined large neuroendocrine cancer in 21 patients (8.8%). Atypical denomatous hyperplasia was found in 2 patients. Conculsions. Classical histological analysis should be focused on detection of early preinvasive epithelial lung cancer lesions. (Abstract truncated at 2000 characters).
Keywords: Biopsija; Biopsy; Carcinoma; Carcinoma In Situ; Diagnosis; diagnostika; Hiperplazija; Hyperplasia; Karcinom; Karcinom in situ; Lung Neoplasms; Metaplasia; Metaplazija; Pathology; pljučne bolezni; Pljučne novotvorbe; pljučni rak